2020
DOI: 10.1111/iju.14424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative recovery after robot‐assisted partial nephrectomy of T1 renal tumors through retroperitoneal or transperitoneal approach: A Japanese single institutional analysis

Abstract: Objective To evaluate the quality of recovery in patients who underwent robot‐assisted partial nephrectomy and to compare the outcomes of the transperitoneal or retroperitoneal approach. Methods This study included 121 patients who underwent robot‐assisted partial nephrectomy under general anesthesia from April 2019 to September 2019 at Tokyo Women’s Medical University, Tokyo, Japan. Quality of recovery was defined according to the QoR‐40 Japanese version. The participants responded to the QoR‐40 Japanese vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Finally, we identified 1323 articles after the initial database search. After screening, 21 studies 4‐18 including 5905 patients (TP‐RAPN: 2482 patients; RP‐RAPN: 3423 patients) were eligible for the analysis. All included studies were retrospective studies and were published between 2013 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we identified 1323 articles after the initial database search. After screening, 21 studies 4‐18 including 5905 patients (TP‐RAPN: 2482 patients; RP‐RAPN: 3423 patients) were eligible for the analysis. All included studies were retrospective studies and were published between 2013 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Overall complication rate data were extracted from 18 studies 13‐17,23‐26 . There are 4499 patients in total with 1692 RP‐RAPN patients and 2807 TP‐RAPN patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-Based Complementary and Alternative Medicine flap artery in patients with diabetes, which is consistent with the conclusion and proves the scientificity of results in this study. At present, many scholars have affirmed the application value of color Doppler ultrasound in the diagnosis of small renal tumors in their research reports, but some clinical trials have revealed that the detection rate and accuracy of single color Doppler ultrasound for small renal tumors are not high, and its application effect remains unsatisfactory [21,22]. SMI is an imaging test that mainly targets at blood flow velocity in microvessels as well as blood flow classification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the indication for PN includes large and complicated tumors if there is technical feasibility for the surgeon according to the National Comprehensive Cancer Network guideline 5,6 . Following the widespread use of the Da Vinci surgical system and the universal health insurance coverage of robot‐assisted PN (RAPN), the number of renal masses treated by RAPN is increasing in Japan 7 …”
Section: Introductionmentioning
confidence: 99%